PENGARUH PEMBERIAN JINTAN HITAM (N.SATIVA) TERHADAP KADAR LDL PADA PASIEN DIABETES MELLITUS TIPE 2 DI RUMAH SAKIT UMUM DAERAH DELI SERDANG - NUZUL MUHAMMAD NASUTION; FANI ADE IRMA (LP2MTBM MAKARIOZ, 2020)
Type 2 Diabetes Mellitus (Type 2 DM) used to be called non- insulin-dependent or adult-onset diabetes caused by noteffective insulin using for the body. In many researches it is found that the amount of incident average of type 2 DMincreases rapidly in the world. Indonesia is one of the country with the most accusative in seven grade of world table. Thedevelompment of this is done on and on by many researches. One of them is the research of black cumin (N.Sativa). It isused to know the influences of cholesterol of DM accusative. The purpose of the study was to determine the effect of givingBlack Cumin (N.sativa) to LDL levels in Type 2 Diabetes Mellitus patients at Deli Serdang General Hospital. This type ofresearch is experimental using pretest post test control group design. Subjects in this study were DM type 2 patients in theDeli Serdang General Hospital with a total of 18 subjects divided into 2 groups namely 9 control group subjects and 9standard group subjects. This research technique uses purposive sampling and data analysis using Paired t-test. Retrievingdata through laboratory results. The average LDL level in the pre-test control group was 109.89 and the average post-testscore was 105.67. In the standard pre-test group the average LDL level was 111.0 and the average post-test score was91.5. There is a significant difference between LDL levels before and after administration of black cumin (N.sativa).